FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK USAHA MENENGAH DALAM MEMENUHI KEWAJIBAN PAJAK PENGHASILAN DI KOTA SAMARINDA - Mirna Widyaningtias Putri; Vera Anitra (Jurnal Ekonomi dan Manajemen, 2017)
The research objective is to determine the level of awareness and understanding of taxation Taxation on tax compliance obligations medium-sized enterprises in income tax in the city of Samarinda. The data collection is done by providing as much as 138 copies kueisoner, but only 45 copies that can be processed. Copies distributed to the finance department or medium-sized business owners in the city of Samarinda. The data obtained and analyzed using SPSS.The results showed that the level of awareness and understanding Taxation Taxation positive and significant impact on Taxation compliance.